PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA ELEMEN BHINNEKA TUNGGAL IKA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SD 29 GANTING - Elin Marlina; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research aims to improve students’ learning outcomes in Civic Education (Pendidikan Pancasila), specifically on the Bhinneka Tunggal Ika element, through the implementation of the Problem Based Learning (PBL) model in Grade V at SD 29 Ganting. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The researcher acted as the teacher, while the classroom teacher served as the observer. Data were collected through observation sheets, documentation, and learning achievement tests. The results showed an improvement in both learning process and learning outcomes. In Cycle I, student learning outcomes were still relatively low, with limited active participation during learning activities. After improvements were made in Cycle II, there was a significant increase in student engagement and achievement. The average score and the percentage of mastery learning improved, indicating that the PBL model effectively enhanced students’ understanding of diversity, tolerance, and unity values in the Bhinneka Tunggal Ika element. Therefore, it can be concluded that the implementation of the Problem Based Learning model can improve students’ learning outcomes in Civic Education.